2020
DOI: 10.3389/fnagi.2020.00121
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Efficacy of Multiple Interventions for Mild Cognitive Impairment in Alzheimer's Disease: A Bayesian Network Meta-Analysis

Abstract: Background: Mild cognitive impairment (MCI) is the early phase of Alzheimer's disease (AD). The aim of early intervention for MCI is to decrease the rate of conversion from MCI to AD. However, the efficacy of multiple interventions in MCI, and the optimal methods of delivery, remain controversial. We aimed to compare and rank the treatment methods for MCI in AD, in order to find an optimal intervention for MCI and a way to prevent or delay the occurrence of AD. Methods: Pair-wise and network meta-analysis were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 56 publications
1
28
1
1
Order By: Relevance
“…Music therapy might be active, such as songwriting, singing, and playing musical instruments, or receptive, such as listening, or both, delivered to individuals or groups, with or without a music therapist. Music therapy was also effective in MCI patients [64]. Though targeting multiple symptom domains seems promising, there has been disagreement between published meta-analyses whether active or receptive treatments have similar effects on specific outcomes [13].…”
Section: Music Therapy (Mt)mentioning
confidence: 99%
See 3 more Smart Citations
“…Music therapy might be active, such as songwriting, singing, and playing musical instruments, or receptive, such as listening, or both, delivered to individuals or groups, with or without a music therapist. Music therapy was also effective in MCI patients [64]. Though targeting multiple symptom domains seems promising, there has been disagreement between published meta-analyses whether active or receptive treatments have similar effects on specific outcomes [13].…”
Section: Music Therapy (Mt)mentioning
confidence: 99%
“…Meta-analytic evidence reported that acupuncture improved cognitive functions in rodent models [72]. Beneficial effects of acupuncture on cognition in clinical trials have also been detected, such as in patients with MCI [64] or in mild, moderate, and severe AD [73]. In the latter population, while acupuncture did not have superior effects compared with drug therapy, acupuncture in combination with pharmacotherapy was beneficial on general cognitive function and activities in daily living [18].…”
Section: Acupuncture Therapy (At)mentioning
confidence: 99%
See 2 more Smart Citations
“…No additional SR was identified by the expert panel members during the voting process. Therefore, 11 eligible SRs were included and analyzed in our study eventually (Lee et al, 2009;Cao et al, 2013;Liu et al, 2014;Zhou et al, 2015Zhou et al, , 2017Deng and Wang, 2016;Kwon et al, 2018;Huang et al, 2019;Kim et al, 2019;Wang et al, 2020;Lai et al, 2020). The contained research evidence of interest was extracted out and further assessed with the help of the GRADE tool.…”
Section: Evidence In the Fieldmentioning
confidence: 99%